Psychological Factors Affecting The Quality Of Online Learning - et. al., Dr Saptorshi Das, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Encompassing some of its unique features, online education has given a new perception of learning processes.This reality prompted research into the features of online learning environments that affect students' learning experiences, and many features were discovered as a result of this initiative. However, most studies only look at one or a few of these variables, and the findings may be conflicting. In this review, the authors include most of the aspects found in the literature in an integrated model in order to decide which aspects have the greatest effect on students' satisfaction and understanding. This research study is aimed to identifythe psychological factors affecting online learningand discuss those factors in a compressive way. Identifying the aspects of online learning requires a number of fundamental concerns that are extremely relevant to educators today. “What are the factors that lead to the glory of online learning?” is the main issue. Two main variables must be defined on priority basis for addressing research questions. Such as, 1) assessing the final outcome and 2) determining the way used by students to learn by utilizing suitable educational resources.The dimensions we investigated in this study were students' mood, affect, motivation, and experience of using an Online Learning Tool. To help us assess these variables, we performed a survey using validated items from previous related research work. Our study was focused on an exploratory factor analysis (EFA).